2021
DOI: 10.34305/jnpe.v2i1.358
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan Remaja Tentang Pendidikan Seks Dengan Perilaku Seks Pranikah Pada Remaja Di SMK Mutiara Insani

Abstract: Perilaku seks pranikah adalah segala tingkah laku yang didorong oleh hasrat seksual baik dengan lawan jenisnya maupun dengan sesama jenis. Salah satu faktor penyebab utamanya yaitu minimnya pengetahuan seks yang benar dan terpadu melalui pendidikan formal maupun non formal. Tujuan penelitian ini adalah untuk mengetahui hubungan pengetahuan remaja tentang pendidikan seks dengan perilaku seks pranikah di SMK Mutiara Insani tahun 2021. Penelitian ini menggunakan Metode observasional analitik dengan pendekatan cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…These results are in line with the research conducted by Putri in 2017 where there is a relationship with the p-value of 0.000 [16]. Research conducted by Egy Pratama also states that there is a relationship between knowledge about sex and premarital sex behavior in adolescents in high school (p-value < 0.01 and OR = 0.583) [7]. In addition, the study also showed that knowledge of reproductive health is related to sexual behavior where the value of p = 0.00 [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in line with the research conducted by Putri in 2017 where there is a relationship with the p-value of 0.000 [16]. Research conducted by Egy Pratama also states that there is a relationship between knowledge about sex and premarital sex behavior in adolescents in high school (p-value < 0.01 and OR = 0.583) [7]. In addition, the study also showed that knowledge of reproductive health is related to sexual behavior where the value of p = 0.00 [17].…”
Section: Discussionsupporting
confidence: 90%
“…Lack of knowledge can be the cause of adolescent premarital sexual behavior [6]. Knowledge of reproductive health, especially for adolescents, needs to be taught, so that adolescents understand how to take appropriate actions to behave and protect their own reproductive health [7]. Attitudes and knowledge of adolescents about reproductive health is something important, the wrong information obtained will make the knowledge and perceptions of adolescents become incorrect too, so that it can be an indicator of an increase in free sex behavior in adolescents [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian ini tidak sesuai dengan penelitian Mulyati, dkk pada tahun 2021 yang meneliti "Hubungan Konsumsi Alkohol Dengan Perilaku Seks Pranikah Pada Remaja Di Kelurahan Karot", dimana hasil penelitian menunjukkan bahwa mayoritas responden yang mengkonsumsi alkohol sebanyak 84 orang (58,3%). Hal ini dikarenakan salah satu alasan responden mengkonsumsi alkohol adalah agar dapat diterima dalam suatu kelompok jadi remaja harus mengikuti kegiatan kelompok yang akan diikutinya dan remaja mengkonsumsi alkohol karena diakibatkan oleh rasa penasaran, ingin tahu (23).…”
Section: Patogenesis Dan Patofisiologiunclassified
“…Kejadian perilaku seks pranikah pada remaja setiap tahun cenderung meningkat hal ini disebabkan oleh beberapa faktor salah satunya adalah kurangnya pengetahuan tentang Pendidikan seks pranikah (Pratama, 2014). Hal ini tentunya menjadi perhatian khusus bagi para orang tua dan tenaga kesehatan bagaimana untuk dapat menekan angka masalah kurangnya pendidikan seks remaja (Irianto, 2014).…”
unclassified